The Potential of Tamarillo (Solanum betaceum) Peel as an Antioxidant by Radical Scavenging DPPH and Antiaging by Collagenase Inhibition - Liena, Liena; Fioni, Fioni; Siregar, Lidya; Girsang, Ermi (Universitas Aisyah Pringsewu, 2023)
Background: The skin aging process, which is impacted by various variables, including genetics, advancing age, environmental conditions, and lifestyle choices, has emerged as a significant concern in skincare. Signs of skin aging, such as decreased firmness and elasticity and the appearance of fine lines and discoloration, have raised significant concerns. The link between free radicals and skin aging has been the subject of in-depth research, while collagenase activity has also been found to influence skin aging. The natural antiaging potential of herbal plants has been widely studied to overcome this problem, one of which is tamarillo (Solanum betaceum). Objectives: This study aimed to examine the antioxidant and antiaging properties of S. betaceum Peel Extract (SBPE). Method: Tamarillo peel was extracted using the maceration method. The antioxidant test was analyzed by trapping 2,2-diphenyl-1-picrylhydrazyl (DPPH), and the antiaging test was analyzed by collagenase inhibitory activity. Results: SBPE showed vigorous DPPH scavenging activity (IC50: 60.91 ± 0.36 ?g/mL), while SBPE also showed moderate collagenase inhibitory activity (IC50: 121.47 ± 2.32 ?g/mL). Conclusion: SBPE has high antioxidant activity and moderate antiaging activity.